Physical simulations of neutral boundary layer in rotating tank - Ferrero, E; Longhetto, A; Montabone, L; Mortarini, L; Manfrin, M; Sommeria, J; Didelle, H; Giraud, C; Rizza, U (2005)
Laboratory measurements of neutral atmospheric boundary layer (ABL) are presented. The experiment was carried out in the large rotating tank of the Coriolis-LEGI laboratory in Grenoble. An ABL was created at reduced scale and measured. The mean flow was generated, both increasing (spin-up) and decreasing (spin-down) the rotation speed of the platform. Preliminary measurements by acoustic probes were used to assess the decay with time of the flow velocity at the position where turbulence measurements were subsequently performed. The mean velocity and the turbulence fields were then measured by using PIV (Particle Image Velocimetry) technique, which allows to obtain high-resolution measurements in the simulated ABL. For each rotation period and velocity conditions, two vertical cross-sections of the flow were measured at different times, then 3D velocity fields were reconstructed from the two planar fields under convenient geometric (orthogonal) and physical assumptions (reproducibility of the flow). The aim of this work is to collect a useful data set for testing and comparing turbulence models and parameterisations. For this reason, particular attention was paid to the turbulence statistics, turbulent fluxes and scales. The results of the data analysis are presented and discussed. © Società Italiana di Fisica.